Antiviral Activity of Silver Nanoparticles Immobilized onto Textile Fabrics Synthesized by Radiochemical Process. Issue 11 (2016) - Seino, Satoshi; Imoto, Yasuo; Kosaka, Tomoya; Nishida, Tomoki; Nakagawa, Takashi; Yamamoto, Takao A.
ABSTRACT: Antiviral activity of metallic Ag nanoparticles immobilized on textile fabrics were investigated. The Ag nanoparticles synthesized by radiochemical process are firmly immobilized on the surface of support textile fabrics of cotton. Small Ag particles of about 2–4 nm were observed together with relatively large particles of more than 10 nm. The Ag nanoparticles showed antiviral activity against Influenza A and Feline Calicivirus. The antiviral activity significantly depended on the concentration of the Eagle's minimal essential medium. It was implied that the surface passivation by inhibitory agent lead to the deactivation of metallic Ag nanoparticles.